Thirty-Day Unplanned Readmission after Total Knee Arthroplasty at a Teaching Community Hospital: Rates, Reasons, and Risk Factors - Workman, Kalain K.; Angerett, Nathan; Lippe, Ronald; Shin, Alex; King, Scott (The Journal of Knee Surgery, 2020)
Unplanned readmission after total knee arthroplasty (TKA) has an increasing prevalence in the United States. Readmissions are now a metric for hospital quality of care, yet there are mixed results and variables associated with unplanned readmission. In this changing healthcare, it is critical for community healthcare institutions to identify risk factors for unplanned readmissions following TKA. Retrospective chart review and a hospital administrative database query to report causes, demographics, and medical comorbid risk factors result in 30-day readmission after undergoing primary TKA between 2011 and 2016 at a teaching community hospital. This study identified 7,482 primary TKA procedures of which 210 (2.8%) were unplanned readmissions. Gastrointestinal bleed (9.05%) and periprosthetic infection (8.10%) were the most common causes of readmission. Age 65 and older (odds ratio [OR], 1.64; 95% confidence interval [CI], 1.21–2.21; p = 0.0012), male (OR, 1.37; 95% CI, 1.03–1.83; p = 0.0302), length of stay > 3 days (OR, 2.04; 95% CI, 1.45–2.86; p < 0.0001), and discharge to rehab (OR, 2.21; 95% CI, 1.49–3.26; p ≤ 0.0001) were correlated significantly with risk of 30-day readmission. Chronic airway disease (OR, 2.81; 95% CI, 1.54–5.14; p = 0.0008) and obesity (OR, 1.45; 95% CI, 1.006–2.10; p = 0.0463) were significant risk factors. Higher Charlson comorbidity index was not a predictor of time to readmission within 30 days after TKA.
Keywords: total knee arthroplasty; readmission; total joint arthroplasty; medical comorbidities